Performance appraisal of industrial waste incineration bottom ash as controlled low-strength material - Razak, H.A.; Naganathan, S.; Hamid, S.N.A. (2009)
Controlled low-strength material (CLSM) is slurry made by mixing sand, cement, ash, and water. It is primarily used as a replacement for soil and structural fillings. This paper presents the findings of a preliminary investigation carried out on the performance of industrial waste incineration bottom ash as CLSM. CLSM mixes were designed using industrial waste incineration bottom ash, and cement. Tests for density, setting time, bleed, and compressive strength on cubes under various curing conditions, corrosivity, and leaching of heavy metals and salts were carried out on the CLSM mixtures, and the results discussed. Compressive strength for the designed CLSM mixtures ranged from 0.1 to 1.7 MPa. It is shown that the variations in curing conditions have less influence on the compressive strength of CLSM at high values of water to cement ratio (w/c), but low values of w/c influences the strength of CLSM. The CLSM produced does not exhibit corrosive characters as evidenced by pH. Leaching of heavy metals and salts is higher in bleed than in leachate collected from hardened CLSM. Cement reduces the leaching of Boron in bleed. It is concluded that there is good potential for the use of industrial waste incineration bottom ash in CLSM. Â© 2009 Elsevier B.V. All rights reserved.